2012
DOI: 10.1007/s00894-012-1428-x
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bond tunability II: the varying roles of electrostatic and dispersion contributions to attraction in halogen bonds

Abstract: In a previous study we investigated the effects of aromatic fluorine substitution on the strengths of the halogen bonds in halobenzene…acetone complexes (halo = chloro, bromo, and iodo). In this work, we have examined the origins of these halogen bonds (excluding the iodo systems), more specifically, the relative contributions of electrostatic and dispersion forces in these interactions and how these contributions change when halogen σ-holes are modified. These studies have been carried out using density funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
147
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(154 citation statements)
references
References 52 publications
6
147
0
1
Order By: Relevance
“…2 and especially in Fig. 7, and can also be seen in earlier reports [27,28,33,81]. They help to explain why hydrogen bonds tend overall to be less directional than other σ-hole interactions [33,96,97].…”
Section: Hydrogen Bondingsupporting
confidence: 55%
See 1 more Smart Citation
“…2 and especially in Fig. 7, and can also be seen in earlier reports [27,28,33,81]. They help to explain why hydrogen bonds tend overall to be less directional than other σ-hole interactions [33,96,97].…”
Section: Hydrogen Bondingsupporting
confidence: 55%
“…Dispersion is commonly considered to be associated with electronic correlation [79][80][81], i.e., the instantaneous correlated movements of the electrons in response to their mutual Coulombic repulsions. These movements create temporary dipoles which interact attractively, accounting for the stabilizing contribution of dispersion.…”
Section: The Nature Of σ-Hole Interactionsmentioning
confidence: 99%
“…The relative magnitudes of these terms are highly dependent upon the identity of the halogen X, with the relative contribution of the electrostatic term increasing for larger X [27]. Recently, Riley et al [32] indicated that halogens with larger, more positive σ-holes tend to exhibit weaker dispersion interactions, which are attributable to the lower local polarizabilities of the larger σ-holes.…”
Section: Introductionmentioning
confidence: 97%
“…Many reviews have described halogen bonding in detail, which is the best-known s-hole interaction. [6,[19][20][21][22] More recently, s-hole complexes with atoms of group IV, the tetrel (Tr) atoms, have been described, [24][25][26][27][28][29] and mostly focus on the heavier Tr atoms as tetrel-bond donors, leaving noncovalent carbon bonding much less studied. [30][31][32] In an sp 3 -hybridized electron-deficient C atom, there is only limited space available for an electron-rich guest molecule to nest itself.…”
mentioning
confidence: 99%